A graph theoretic approach for supply chain coordination. Issue 4 (19th July 2006) - Kaur, Arshinder; Kanda, Arun; Deshmukh, S.G.
Supply chain coordination is an effective approach to manage the dependencies among supply chain members. These members often try to achieve their respective objectives, disregarding the objective of the complete supply chain. This results in higher supply chain costs, greater lead times and a large variance between supply and demand. Supply chain coordination is defined as the joint effort of the supply chain members towards mutually defined goals. There are a number of mechanisms to achieve coordination. The existing literature lacks in presenting a comprehensive measure of supply chain coordination. In this paper, an attempt has been made to identify various mechanisms of coordination. A graph theoretic approach is used to model various mechanisms of coordination and their interdependencies. The digraph representing the supply chain coordination is converted to its adjacency matrix whose permanent function gives a composite index of coordination. This approach helps compare organisations in terms of their coordination capability.